Biological Evaluation of Garcinia kola Heckel - Abdulrahman Mahmoud Dogara; Saber W. Hamad; Harmand A. Hama; Sarwan W. Bradosty; Soran Kayfi; Sawsan S. Al-Rawi; Abubakar Abdullahi Lema (Advances in Pharmacological and Pharmaceutical Sciences)
Garcinia kola belongs to the Garcinia genus of the Clusiaceae family and Malpighiales order. It contains more than 180 members all over the globe. It is found all over Asia and in tropical African countries. In Africa, traditionally, G kola is used to manage and treat cancer, diabetes, malaria, analgesics, hypertension, and other numerous ailments. This review aimed to comprehensively update relevant information regarding the pharmacological potential of Garcinia kola. Electronic databases such as ScienceDirect, PubMed, Wiley, Google Scholar, Hindawi, and Springer extracted valuable information from original scientific research papers. Inclusion Criteria. Antioxidant, antimicrobial, antidiabetic, antibacterial, medications, antiviral, traditional medicine, ethnopharmacology, toxicity, cytotoxic action, chemical composition, mineral elements, GCMS analysis, and any other related phrases were used as filters to find studies. Exclusion Criteria. Data from questionable online sources, as well as thesis reports and review publications, were excluded from this investigation. The investigation revealed that seeds of G. kola are very efficient as antioxidant, antimicrobial, antidiabetic, antihypertension, antianalgesic, and anti-inflammatory. The study also found that too much consumption of the seeds caused low fertility and toxicity. However, the safety and efficacy of G. kola have not been wholly assessed in humans, and further well-designed clinical trials are needed to corroborate preclinical findings. The mechanism of action of the seed extract should be examined. The standard dose and safety of the seed should be established.